Informatization as an aesthetic strategy of modern screen culture - Yevhen Vorozheikin (Cхід, 2016)
This work is aimed to identify the cultural changes that have occurred as a result of informatization. The article investigates the strategies of contemporary screen culture aimed to satisfy human needs in information. The analysis of technical improvement of information possibilities of screen media is based on J. D. Bolter's and R. Grusin's theory of remediation. The article identifies informational potentials of visual novel (contemporary TV series), which is the result of remediation of TV, movie and literary novel. In addition, the article investigates the process of informatization by means of screen space formation or, in other words, by screen aesthetics. The article identifies and analyzes the hybridization strategy and the strategy of visual eclecticism. Hybridization strategy is a method to combine information of different nature, whereupon more truthful visual stories are created. It is mainly used in movies and video games. The strategy of visual eclecticism that allows viewers (users) to perceive multiple information flows, mainly related to the screen space of modern television.